PERAN SISTEM INFORMASI MANAJEMEN TERHADAP BROKER ASURANSI - Dea Aulia Syahputri; Dini Vientiany; Fajri Romadhoni; Muhammad Fauzan (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The role of management information systems in insurance programs is very important. This system makes it easier for brokers to manage customer data, including personal information and insurance needs. In addition, the management information system helps brokers in handling the customer claim submission process and ensures that claim submissions are handled correctly by the broker and insurance company. Overall, the management information system supports brokers in managing data and increasing the efficiency of managing risks and insurance needs.